2022
DOI: 10.3390/ph15030297
|View full text |Cite
|
Sign up to set email alerts
|

MiR-486-5p Targets CD133+ Lung Cancer Stem Cells through the p85/AKT Pathway

Abstract: Despite improvements in therapies and screening strategies, lung cancer prognosis still remains dismal, especially for metastatic tumors. Cancer stem cells (CSCs) are endowed with properties such as chemoresistance, dissemination, and stem-like features, that make them one of the main causes of the poor survival rate of lung cancer patients. MicroRNAs (miRNAs), small molecules regulating gene expression, have a role in lung cancer development and progression. In particular, mir-486-5p is an onco-suppressor miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…miR-486 is transcribed from the intron of the host gene ANK1 (Ankyrin 1) on human chromosome 8p11.21 [29]. There have been many reports describing miR-486-5p (the guide strand) in various cancer types [30][31][32][33]. Previous studies showed that the expression of miR-486-5p was reduced in cancer tissues, and that it functions as a tumor suppressor in breast cancer, colorectal cancer, gastric cancer, hepatocellular carcinoma, and renal cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…miR-486 is transcribed from the intron of the host gene ANK1 (Ankyrin 1) on human chromosome 8p11.21 [29]. There have been many reports describing miR-486-5p (the guide strand) in various cancer types [30][31][32][33]. Previous studies showed that the expression of miR-486-5p was reduced in cancer tissues, and that it functions as a tumor suppressor in breast cancer, colorectal cancer, gastric cancer, hepatocellular carcinoma, and renal cell carcinoma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Among non-coding RNA, miRNAs have been recognized as one of the major regulatory gene families during both normal development and carcinogenesis [ 34 ]. It has been demonstrated that miRNAs can act as both tumor suppressors [ 35 , 36 , 37 ], as well oncogenic miRNAs [ 36 , 38 , 39 ] in several types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR-486-5p, a muscle-enriched miRNA found abundantly in plasma ( BayĂ©s-Genis et al, 2018 ; Small et al, 2010 ) , demonstrates differential expression patterns across various cancers. It is downregulated in lung cancer ( Moro et al, 2022 ), steroid-induced osteonecrosis of the femoral head (SOFNH) ( Chen et al, 2023 ), papillary thyroid carcinoma ( Ma et al, 2016 ), breast cancer ( Li et al, 2019 ) and non-small cell lung cancer serum ( Xing et al, 2020 ), while being upregulated in cervical cancer ( Li et al, 2018 ) and sepsis patient serum ( Sun & Guo, 2021 ).…”
Section: Survey Methodologymentioning
confidence: 99%